2022
DOI: 10.1108/lodj-10-2021-0473
|View full text |Cite
|
Sign up to set email alerts
|

Followership: a review of current and emerging research

Abstract: PurposeOver time, the role of followers within leadership discourse has gained greater status, leading to followers being acknowledged as significant actors in the leadership process. This has led to the development of follower-centric leadership studies, as well as the more emergent research area of followership, with followership research having the specific intention to find out about followers from the perspective of followers. In this paper, the authors provide a review of role-based followership approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, the results of the present study showed that excessively high followership could also reduce the impact of E-Leadership on employee innovation, in line with the finding that ambidextrous leadership suppressed innovation behavior among followers (S. Wang et al, 2021). Therefore, the present study also supplemented and enriched the theoretical knowledge of followership (Bastardoz & Van Vugt, 2019;Matshoba-Ramuedzisi et al, 2022;Plachy & Smunt, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, the results of the present study showed that excessively high followership could also reduce the impact of E-Leadership on employee innovation, in line with the finding that ambidextrous leadership suppressed innovation behavior among followers (S. Wang et al, 2021). Therefore, the present study also supplemented and enriched the theoretical knowledge of followership (Bastardoz & Van Vugt, 2019;Matshoba-Ramuedzisi et al, 2022;Plachy & Smunt, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…For others, the legitimation that government policy provides may cloak other agendas that may have less to do with implementation of policy, and more to do with exerting control over others. Specifically, the public sector's primary reliance upon managerial control mechanisms has compromised and deteriorated public leaders' relationships with their followers [61,62]. Furthermore, the focus within traditional leadership approaches upon personality traits, behavioral styles or identifying types of leaders with associated people management techniques [63,64] reinforces a leader-hero myth of leaders working their magic [65] to successfully subject followers to an apparatus of control.…”
Section: The Relational Leadership Modelmentioning
confidence: 99%
“…Leaders can influence how employees interpret information by manipulating goal framing. Research has shown that employees' attitudes and behaviors can be changed based on the positive or negative language used by leaders [30]. When leaders clarify the significance of work and provide contextual information to employees, they can influence their motivation for followership and behavior through specific responsive language forms and symbols [31].…”
Section: Goal Framingmentioning
confidence: 99%